KLAUSA TANPA KATA KERJA (VERBLESS CLAUSE) DALAM JURNAL THE POPULAR CULTURE STUDIES JOURNAL VOLUME 6 NOMOR 1 TAHUN 2018 (SUATU ANALISIS SINTAKSIS) - MAALUA, ERWIN GRENIER; PAKASI, JENNY HILDA; RANUNTU, CHRISTIAN G. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACT            This research entitled ?Verbless Clause in The Popular Culture Studies Journal Volume 6 Number 1 2018 (A Syntactical Analysis),? is written to identify, classify and analyze the types of verbless clause found in the journal. Verbless clause is a clause which does not have a verbal form. Sometimes, it only consists of noun phrase or adjective phrase. Many times, the verbless clause  lacks a subject and it can be seen as a clause with a form of verb be has been omitted (Aarts and Aarts, 1982:85). This study aims at identifying, classifying and analyzing the structure of verbless clause and reduced clause types. The method used in this study is a qualitative descriptive method by Kothari (2004). The data were taken from three different articles in The Popular Culture Studies Journal Volume 6 Number 1 2018. Those articles are: Dance with the Devil: Representations of Femininity, Masculinity, and the Boss-from-Hell in Two Parallel Films; Brick-olage and the LEGO/Brand Axis; and Drunk and Diverse: Reframing the Founding Fathers. All the collected data were identified, classified and analyzed by using Aarts and Aarts theory (1982) and Phillips (2000). The results of this research show that there are 40 verbless clauses found in the journal, consisting 21 verbless clauses with an explicit subject and 19 verbless clauses without an explicit subject. In addition, there are 25 reduced clauses included as a part of verbless clause types.        Keywords: Syntax, Verbless Clause, Pop Culture